Upaya Meningkatkan Kedisiplinan Siswa dalam Mematuhi Atribut Seragam Sekolah Melalui Pelaksanaan Upacara Bendera di MI Darussalam - Cahya, Afina Dwi; Ibda, Hamidulloh (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2024)
The aim of this research is to evaluate efforts to increase student discipline in complying with school uniform attributes through holding a flag ceremony at MI Darussalam. Student discipline in complying with the attributes of school uniforms is very important, because school uniforms are the identity and representation of educational institutions. The research method used was classroom action research involving students in grades 4 and 5. This research was carried out in three stages, each consisting of planning, implementing actions, observing and reflecting. The research results show that regular and consistent flag ceremonies can increase students' discipline in complying with school uniform attributes. At the start of the research, only a small percentage of students complied with the school uniform attributes. However, after three research periods, the proportion of students following the same characteristics increased significantly. Apart from that, this research also revealed that effective communication between teachers and students as well as active participation of students in planning and implementing the flag ceremony positively affected student discipline. Based on the research results, it is recommended that the flag ceremony at MI Darussalam continue to run well and consistently. Apart from that, it is also necessary to provide more intensive outreach to students about the importance of paying attention to the attributes of school uniforms. It is hoped that students' discipline in complying with school uniform attributes can improve with this effort.